Detection and identification of Mucorales and Aspergillus in paraffin-embedded samples by real-time quantitative PCR - Jiang, Xiaolin; Jiang, Yong; Ye, Feng (Frontiers in Cellular and Infection Microbiology, 2023)
Background: In this study, we used real-time quantitative PCR (RQ-PCR) to rapidly detect Mucorales and Aspergillus in formalin-fixed, paraffin-embedded (FFPE) samples, targeting 18SrRNA gene and 28SrRNA gene. Identification of Mucorales and Aspergillus was analysed by combining Mucorales RQ-PCR (Mucorales18SrRNA and Mucorales28SrRNA) with Aspergillus RQ-PCR (Aspergillus18SrRNA and Aspergillus28SrRNA). Objectives: The aims of this study were to compare the diagnostic performances of four RQ-PCR assays as single and combined diagnostic and identification tools. Methods: We collected 12 control group samples and 81 experimental group samples diagnosed by histopathology, including mucormycosis (19 patients, 21 FFPE samples), aspergillosis (54 patients, 57 FFPE samples) and mucormycosis with aspergillosis (3 patients, 3 FFPE samples). All samples were detected by four RQ-PCR tests to compare and analyze diagnostic performance. Results: The sensitivities of Mucorales18SrRNA and Mucorales28SrRNA were both 75%, with the tests having specificities of 97.10% and 94.20%. The sensitivities of Aspergillus18SrRNA and Aspergillus28SrRNA were 73.33% and 65%, with the tests having specificities of 87.88% and 81.82%. The values of the evaluation indexes of the combined detection of Mucorales28SrRNA and Aspergillus18SrRNA (M28A18) were the highest with a kappa coefficient value of 0.353, followed by M18A18. M28A18 had a sensitivity of 67.90% and a specificity of 100%. Conclusions: We recommend using the combination of Mucorales RQ-PCR and Aspergillus RQ-PCR as a screening tool to detect samples suspected of mucormycosis and/or aspergillosis.